Development of Cooperative Learning-Based Student Worksheets (LKPD) on Chemical Nomenclature Subject Material for 10th Grade Students - Septiana, Tri Merry; Sartika, Rody Putra; Rasmawan, Rahmat (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Abstract Research has been done to develop a product in the form of student worksheets chemical compounds for SMA/MA grade X. This research aims to develop students ' worksheets of material nomenclature for SMA/MA grade X, knowing the quality of teaching materials based on expert test (expert judgement), knowing student response, and knowing the implementation of learning process. This research and development (R&D) is conducted based on 4-D models that are limited to the develop stage. The subject of this study is the LKPD based on cooperative learning in compound nomenclature. The product is in the quality of one chemical teacher, one Indonesian teacher, and two chemistry lecturers. Based on the results of the expert quality assessment, the LKPD based cooperative learning in compound name matter got very good/very high category with a percentage of 84.27% worth using as a teaching material in the learning process. Â  Keywords: LKPD, Cooperative Learning, feasibility of the product